Germination and hormonal balance in Vitro of Astronium Urundeuva (M. Allemão) Engl. - Silva, Leonardo Maximo; Oliveira, Leandro Silva de; Nogueira, Ariane da Silva; Souza, Nayara dos Santos de; Jorge, Nicole Vieira; Honorato, Glenda Araújo de Souza; Silva, Leovandes Soares da (Brazilian Journal of Production Engineering, 2023)
Aroeira-do-sertão (Astronium urundeuva) has applicability for therapeutic purposes due to its pharmacological characteristics and the wood used due to its resistance and excellent durability. Due to the intense exploitation, is included on the endangered species list. A micropropagation is a potential tool for in vitro propagation and species conservation. Therefore, this work aims to evaluate the germination and effect of different concentrations of ANA associated with TDZ and BAP on the in vitro multiplication of A. urundeuva. Explants were nodal segments obtained from seedlings germinated in vitro. They were inoculated in MS50% culture medium, supplemented with the concentrations of ANA (0.0; 0.025, and 0.050 mg.L-1), TDZ (0.0; 0.25; 0.50; 0.75, and 1.00 mg.L-1) and BAP (0.0; 0.25; 0.50; 0.75, and 1.00 mg.L-1). After 31 days, we evaluated the vigor of explants, calluses, and the number of sprouts. The in vitro germination of A. urundeuva seeds was 61%, demonstrating that micropropagation is a feasible technique to initiate. The explants supplemented only with BAP showed greater vigor. However, TDZ induced physiological disorders in the explants, such as intense callosities and subsequent tissue necrosis. The auxin/cytokine hormonal balance was not favorable for the in vitro multiplication of the species.